The relation between social support, anxiety and distress symptoms and maternal fetal attachment. (8th August 2018) - Hopkins, Joyce; Miller, Jennifer L.; Butler, Kristina; Gibson, Lynda; Hedrick, Laura; Boyle, Deborah Anne
Abstract: Objective: The aims of this study were to: (1) examine the relation between social support, trait anxiety, symptoms of maternal distress (including stress, depression and anxiety) and maternal–fetal attachment; and (2) to determine if social support buffers the relation between trait anxiety, symptoms of distress and maternal–fetal attachment. Design: Ninety-four pregnant women completed five self-report questions. Two hierarchical regression analyses were conducted to examine the influence of trait anxiety, symptoms of distress, and social support on two factors of maternal–fetal attachment, quality and intensity/frequency. Results: In the first model with the dependent measure as the maternal–fetal attachment quality score, trait anxiety ( β = –.24, p < .05) and social support ( β = .30, p < .01) were significant predictors, accounting for 18% of the variance. In the second model with the dependent measure as the maternal–fetal attachment intensity/frequency score, trait anxiety ( β = –.23, p < .05) and social support ( β = .32, p < .01) were significant predictors, accounting for 23% of the variance. In addition, the interaction term contributed a significant 4% of the variance, indicating that when social support is high, the relation between anxiety and maternal–fetal attachment intensity/frequency is attenuated. Conclusions: This study demonstrates that prenatal attachment is related to trait anxiety and social support. These findings suggest that interventions to decrease anxiety and increase social support could enhance maternal–fetal attachment.